Banks' foreign homes - Kirsten Schmidt; Lena Tonzer (Deutsche Bundesbank, 2024)
We study whether the low interest rate environment paired with booming housing markets affected banks' foreign activities in terms of commercial and residential real estate backed lending. Using a unique dataset covering systemically relevant banks in the euro area over the period 2015-2022, we find that banks expand their foreign real estate backed lending in the presence of higher lending spreads. The result is especially present given a lack of or misalignment in macroprudential policies across home and destination country. Furthermore, we assess whether banks disclose potential losses conditional on higher lending spreads and borrowing country exposure. We find only better capitalized banks to show higher forbearance ratios. In line with search-for-yield motives, we find that during the COVID-19 crisis low capitalized banks experienced larger loan losses on real-estate backed loans in countries having offered higher rates.
Keywords: F21; F34; G10; G21; 330; International banking; real estate backed loans; macroprudential regulation; financial stability